Writing business bids and proposals for dummies - Cobb, Neil (--For dummies., 2016)
Congratulations! You have in your hands the collected knowledge and skills of the professional proposal writer -- without having to be one! Inside, you'll find out how to unlock what these professionals know and apply it to your own business to improve the way you capture new customers and communicate with existing ones! --Publisher.